Eukaryotic viruses in the fecal virome at the onset of type 1 diabetes: A study from four geographically distant African and Asian countries. Issue 4 (7th April 2021) - Cinek, Ondrej; Kramna, Lenka; Odeh, Rasha; Alassaf, Abeer; Ibekwe, Mary Ann Ugochi; Ahmadov, Gunduz; Elmahi, Bashir Mukhtar Elwasila; Mekki, Hanan; Lebl, Jan; Abdullah, Mohammed Ahmed
Abstract: Objectives: Studies of the fecal virome in type 1 diabetes (T1D) have been limited to populations of Europe and the United States. We therefore sought to characterize the stool virome in children after onset of T1D and in matched control subjects from four geographically distant African and Asian countries. Methods: Samples of stool were collected from 73 children and adolescents shortly after T1D onset (Azerbaijan 19, Jordan 20, Nigeria 14, Sudan 20) and 105 matched control subjects of similar age and locale. Metagenomic sequencing of the DNA and RNA virome was performed, and virus positivity was defined as more than 0.001% of reads of the sample. Selected viruses were also quantified using real‐time PCR. Conditional logistic regression was used to model associations with eukaryotic virus positivity. Results: Signals of 387 different viral species were detected; at least one eukaryotic virus was detected in 71% case and 65% control samples. Neither of observed eukaryotic virus species or genera differed in frequency between children with T1D and controls. There was a suggestive association of the total count of different viral genera per sample between cases (1.45 genera) and controls (1.10 genera, OR 1.24, 95%CI 0.98–1.57), and an unplanned subanalysis suggested marginally more frequent endogenous retrovirus signal in cases (in 28.8% vs. in 8.6% controls, OR = 4.55, 95%CI 1.72–12). Conclusions: No clear and consistent association with T1D was observed in the fecal viromes from four distant non‐European populations. The finding of borderline associations of human endogenous retroviruses merits further exploration.